In vitro alpha-amylase and alpha-glucosidase inhibitory activities of fruits of ficus auriculata lour. - NISHAT ANJUM; Y.C. TRIPATHI (International Journal of Pharma and Bio Sciences, 2019)
The present study was aimed to investigate the phytochemical composition and in-vitro substantiation of α-amylase and α-glucosidase enzymes inhibitory activity of the fruits of Ficus auriculata Lour. The fruits were first extracted with methanol:water (4:1) and the extract obtained was fractionated using n-butanol (BuOH), ethylacetate (EtOAc), methanol (MeOH) and water (Aqueous). All the four fractions were phytochemically screened for presence of various phytochemical groups. Different concentrations (50-500 mg/mL) of fractions were subjected to α-amylase and α-glucosidase inhibitory assay and percentage inhibition as well as IC50 values were calculated. Phytochemical screening indicated highest number of different phytochemicals in the methanol fraction followed by EtOAc and aqueous fractions. All fractions exhibited inhibitory action against α-amylase and α-glucosidase enzymes in a concentration dependant manner. The BuOH, EtOAc, MeOH and aqueous fractions recorded 58.39, 78.98, 91.45, and 75.25 % inhibitory activities against α-amylase and 66.37, 84.66, 97.75, and 79.55 % against α-glucosidase at a concentration of 500 μg/mL, which is the highest among all tested doses. Among all, methanol fraction recorded the maximum α-amylase and α-glucosidase inhibitory activity with an IC50 value of 161.73±0.43 and 103.43±0.67 respectively comparable with that of acarbose (155.08±1.75 and 95.63±1.71 mg/mL). The results have evidently shown F. auriculata fruits as potent α-amylase and α-glucosidase inhibitor. The enzyme inhibitory potentiality of the specific fraction of F. auriculata fruits could be beneficially exploited in the treatment of Type 2 Diabetes Mellitus (T2DM). However, characterization of specific phytoconstituents responsible for the activity as well as in vivo studies is needed for further confirmation.